2018
DOI: 10.20944/preprints201810.0594.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

User Satisfaction in Augmented Reality-Based Training Using Microsoft HoloLens

Abstract: With the recent developments in augmented reality (AR) technologies comes an increased interest in the use of smart glasses for hands-on training. Whether this interest is turned into market success or not depends at the least on whether the interaction with smart AR glasses satisfies users, an aspect of AR use that so far has received little attention. With this contribution, we seek to change this. The objective of the article, therefore, is to investigate user satisfaction in AR applied to three cases of pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…After completing both groups of tests, each participant was asked to fill in the demographic survey and a Likert questionnaire in terms of usability, functionality, and technology acceptance. The Likert questionnaire, shown in Table 2, comprises 9 items, each evaluated using a seven-point monotone Likert scale (from 1 = strongly disagree, to 7 = strongly agree) as previously done in [54] and in [55].…”
Section: B Qualitative Assessment Of the Ar Platformmentioning
confidence: 99%
“…After completing both groups of tests, each participant was asked to fill in the demographic survey and a Likert questionnaire in terms of usability, functionality, and technology acceptance. The Likert questionnaire, shown in Table 2, comprises 9 items, each evaluated using a seven-point monotone Likert scale (from 1 = strongly disagree, to 7 = strongly agree) as previously done in [54] and in [55].…”
Section: B Qualitative Assessment Of the Ar Platformmentioning
confidence: 99%
“…The development of the analyses will be based on the study of Xue et al (2019) [ 62 ] that established a set of norms for the evaluation of user satisfaction of using AR glasses and AR applications. Moreover, most of the studies are focused on ergonomic analysis, meanwhile, the research on the aesthetics of interface layout was insufficient as it was claimed in Deng and Wang (2020) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be mentioned that three other types of AR glasses were tested, as during preliminary tests, namely Meta 2, Epson Moverio BT-200 (used e.g., by Angrisani et al, 2018 [ 22 ]), Epson Moverio BT-300, and the Google Glass. Only HoloLens was chosen for the in-depth study (used e.g., by Ingeson et al, 2019 [ 15 ]; Müller et al, 2018 [ 17 ]; Kot et al, 2018b [ 24 ]; Vorraber et al, 2019 [ 28 ]; Sluganovic et al, 2017 [ 58 ]; Xue et al, 2019 [ 62 ]) and presented the most advanced technology with the widest vision field and 3D space, giving the most user-friendly interface, especially in accordance with the assumptions made in this research. Because of the assumptions mentioned above, the AR support system was not adapted and installed on other models of AR glasses.…”
Section: Technology Imperfections Limitations and Future Developmentioning
confidence: 99%
“…These findings are consistent with previous studies indicating that females mostly focus on the usefulness of the system and males focus on the usability of the system. (Xue, Sharma and Wild, 2018). In this context, it can be said that natural interaction affects satisfaction due to the perceived usefulness in females and decreases intrinsic cognitive load by increasing the performance-oriented usage frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that manual interaction using Leap Motion gesture tracking in a stereoscopic environment is more similar to the interaction in the real-world scenario, and therefore this technique provides a high level of natural interaction. Xue, Sharma and Wild (2018) found that females with good computer knowledge who use Virtual Reality goggles and AR-based digital materials had a higher satisfaction score than males. Extraneous load, also referred to as mental effort, occurs when the amount of unnecessary information in the learning memory increases and does not help learning.…”
Section: Introductionmentioning
confidence: 95%